2016
DOI: 10.3389/fpsyg.2016.01501
|View full text |Cite
|
Sign up to set email alerts
|

The Neural Correlates Underlying Belief Reasoning for Self and for Others: Evidence from ERPs

Abstract: Belief reasoning is typical mental state reasoning in theory of mind (ToM). Although previous studies have explored the neural bases of belief reasoning, the neural correlates of belief reasoning for self and for others are rarely addressed. The decoupling mechanism of distinguishing the mental state of others from one’s own is essential for ToM processing. To address the electrophysiological bases underlying the decoupling mechanism, the present event-related potential study compared the time course of neural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 39 publications
2
13
0
Order By: Relevance
“…In addition, some studies have demonstrated that the LPC is associated with the theory of mind (ToM), which is an ability to think about and reason the mental states of both themselves and others. Researchers have proposed that both the belief and desire for reasoning for others are connected with an enhanced LPC ( Geangu et al , 2013 ; Jiang et al , 2016 ). Compared to proselfs, the prosocials have stronger ToM ability and altruistic motivations for others (Van Lange, 2000; Derks et al , 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some studies have demonstrated that the LPC is associated with the theory of mind (ToM), which is an ability to think about and reason the mental states of both themselves and others. Researchers have proposed that both the belief and desire for reasoning for others are connected with an enhanced LPC ( Geangu et al , 2013 ; Jiang et al , 2016 ). Compared to proselfs, the prosocials have stronger ToM ability and altruistic motivations for others (Van Lange, 2000; Derks et al , 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, an fMRI study by Vogeley et al (2001) found that taking a self-perspective led to increased activity in the left temporal polar while modelling the mind of someone else led to increased activity in the right TPJ, respectively. Moreover, relevant ERP studies found a consistent divergence of ERP waveforms between mental states reasoning for self and for others (Jiang, Li, et al, 2016; Jiang, Wang, et al, 2016). These evidences suggested neural overlap as well as distinction in intention reasoning for self and for others.…”
Section: Introductionmentioning
confidence: 86%
“…Based on the preceding review (Carrión et al, 2010; Gagnon et al, 2016; Wang et al, 2012, 2014), we expect that the ERP components associated with the intention reasoning might appear in the later time window after 400 ms onset of stimulus. In addition, with respect to decoupling effects observed in previous ERP studies on ToM reasoning for different agents (Jiang, Li, et al, 2016; Jiang, Wang, et al, 2016), we expect that the ERP waveforms will be differentiated between intention reasoning for self and for others.…”
Section: Introductionmentioning
confidence: 96%
“…The mPFC contains vmPFC and dmPFC. The vmPFC has typically been associated with self-referential processing, and the dmPFC has typically been associated with others-referential processing (Abu-Akel and Shamay-Tsoory, 2011 ; Denny et al, 2012 ; Jiang et al, 2016 ; Molenberghs et al, 2016 ). In our computational model, the mPFC is used to store the result of belief reasoning from ACC: the vmPFC stores the result of self-belief reasoning, and the dmPFC stores the other's belief reasoning.…”
Section: Methodsmentioning
confidence: 99%
“…As indicated in Green et al (2015) and Jiang et al (2016), the specific roles that brain areas have in the mentalization processes is not clear. Based on the neuroimaging studies as described above, we propose four pathways for robots learning from self-experience and uses it in the false-belief task, they are self-experience learning pathway, motivation understanding pathway, reasoning about one's own belief pathway and reasoning about other people's belief pathway.…”
Section: Architecture Of the Brain-tom Modelmentioning
confidence: 99%